Perancangan Website Company Profile PT. Jamkrida Kalimantan Timur - Novia Rahmadana; Al Janatul Ulvivianti; Soniah Soniah; Shinta Selfia; Muhammad Taufiq Sumadi (Jurnal Pengabdian Masyarakat Nusantara, 2023)
one of the media for conveying information about a company or government agency is a company profile website. During operation, PT. Jamrkida East Kalimantan they only rely on the sales team to be able to promote the company and its products to the surrounding community by still using company profile brochures. To deal with the problems faced, we provide input and recommendations for website design at PT. Jamkrida East Kalimantan. The method that will be used in developing this website is to use the prototyping method. The result of this service is to produce a user interface design and prototype of company profile website of PT. Jamkrida East Kalimantan.